2014
DOI: 10.1007/s00170-014-5689-7
|View full text |Cite
|
Sign up to set email alerts
|

Realistic simulation of surface defects in five-axis milling using the measured geometry of the tool

Abstract: Managing macro and micro geometry of surfaces during manufacturing processes is a key factor for their following uses. Indeed micro-geometry and surface topography are directly linked to the performances of functions (contact, friction, lubrication, etc.) by texture parameters to ensure the desired local geometry. Common models for simulation of surface topography are based on ideal geometry of the machining tool and cannot represent surface defects. The actual prediction and simulation of defects is one step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…(Wang et al, 2006) developed a mixed lubrication model for non-Gaussian rough surfaces and optimized the pattern by correcting grooves, skewness, area ratio, and load ratio. Along with experimental analysis, a theoretical model was developed by (Lavernhe et al, 2014) using multi-scale areal analysis for three axis ball-end milling for predicting tool path.…”
Section: Introductionmentioning
confidence: 99%
“…(Wang et al, 2006) developed a mixed lubrication model for non-Gaussian rough surfaces and optimized the pattern by correcting grooves, skewness, area ratio, and load ratio. Along with experimental analysis, a theoretical model was developed by (Lavernhe et al, 2014) using multi-scale areal analysis for three axis ball-end milling for predicting tool path.…”
Section: Introductionmentioning
confidence: 99%
“…If we consider the Z-buffer or N-buffer methods applied to a realistic description of both the tools and the machining path, earlier work have shown that it is possible to simulate the resulting geometry on small portions of the surface in a few minutes [8,9]. Simulation results are very close to experimental results but the simulated surfaces have an area of a few square millimeters with micrometer resolution (Fig.…”
Section: Introductionmentioning
confidence: 52%
“…Some of them are based on partitioning the space whether by lines [6], by voxels [5] or by planes [11], other are based on meshes [3]. Previous works have shown that it is possible to simulate the resulting geometry of the surface with Z-or N-buffer methods applied to a realistic description of both the tools and the machining path in a few minutes [7]. Simulation results are very close to experimental results but the simulated surfaces have an area of some few square millimeters with micrometer resolution.…”
Section: Introductionmentioning
confidence: 99%